Immediate and Long-Term Results of Surgical Treatment of Postcoarctation Aneurysms of Aorta - Tarasenko, Yurii M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Postcoarctation aneurysm is one of the most dangerous complications in the long-term period after surgery for coarctation of the aorta (CoA). Postcoarctation aneurysm formation is associated with high risk of aneurysm rupture, and, therefore, of patient death. Considering high risk of this pathology, it is necessary to study thoroughly the results of surgical treatment and quality of life after the correction and to develop measures to prevent the aneurysms formation. The aim. To present and analyze immediate and long-term effects of treatment of postcoarctation aneurysms of aorta. Materials and methods. We analyzed the long-term results of surgical treatment of postcoarctation aneurysms for 25 years of follow-up (1995–2020). We performed comparative analysis of the results of postcoarctation aneurysms surgical correction. Ninety-one patients were included in the study. All the patients were divided into two groups. Group I included 69 (75.8%) patients who underwent open surgical intervention. Group II included 16 (17.6%) patients who, in turn, were divided into two subgroups: group ІІ-A (5 patients) who underwent endovascular intervention, and group ІІ-B (11 patients) who received hybrid treatment of the discussed pathology. We studied and summarized the results of assessment of the quality of life in the operated patients in a long-term period using SF-36 questionnaire. Results. The study showed that postcoarctation aneurysms most often developed in patients operated for CoA by indirect isthmoplasty procedure (53.5%, n=31). Aneurysms most frequently developed due to the tear of the lower edge of the patch. Better results of surgical treatment were reported in patients of group ІІ. Average period from correction of CoA till correction of postcoarctation aneurysm was 22 years. The postoperative 30-day mortality in all the operated patients (n=85) was 8.2%. The causes of death were as follows: infectious complications in 4 patients (57.1%), hemorrhage in 3 patients (42.9%). Long-term results were observed in 93.5% patients (n= 79). Treatment results were good in 54 patients (68.3%), satisfactory in 16 patients (20.2%), and unsatisfactory in 7 patients (8.9%). Two (2.5%) patients died in the long-term follow-up period. Conclusions. It was established that after indirect isthmoplasty, the cause of the formation of postcoarctation aneurysm was mostly a tear in the lower edge of the patch. It is interesting to note that the younger were the patients by the time of coarctation correction, the longer was the period till the correction of postcoarctation aneurysm. The performed surgical interventions in postcoarctation aneurysms proved to be highly effective in the long term, and the assessment of long-term results in non-operated patients showed their necessity. Long-term quality of life assessment showed significant improvement. There was improvement in the parameter for physical functioning by 26.2%, for general health by 40.7%, and for everyday activities by 36.0%.